THE CO2-H2O SYSTEM. II. CALCULATED THERMODYNAMIC MIXING PROPERTIES FOR 400°C, 0-400 MPA - EXPERIMENTAL DETERMINATION OF P-V-T-X PROPERTIES IN THE CO2-H2O SYSTEM TO 6 KB AND 700°C - Blencoe J.G.; Seitz J.C.; Anovitz L.M. (My University, 1999)
An excess molar volume (Vex)-explicit virial equation, and two empirical Vex expressions developed from experimentally determined densities, were used to calculate excess Gibbs free energies (Gex) and activity-composition (a-X) relations for CO2-H2O fluids at 400°C, 0-400 MPa. Excess Gibbs free energies are continuously positive and asymmetric toward H2O at all pressures up to 400 MPa, rising to peak values of approximately 1300, 1800, 2000 and 2100 J . mol-1 at 50, 100, 200 and 400 MPa, respectively. Calculated activities for H2O and CO2 vary correspondingly, increasing substantially from 0 to 100 MPa, moderately from 100 to 200 MPa, and slightly from 200 to 400 MPa. In addition, because Gex is asymmetric toward H2O, a-X relations for H2O are distinctly different from those for CO2. These results indicate that CO2-H2O fluids are strongly nonideal at 400°C and all pressures above ~30 MPa, despite the fact that peak values for Vex decrease from ~50 cm3 . mol-1 at 30 MPa to ~1 cm3 . mol-1 at 200 MPa, and remain small to pressures at least as high as 500 MPa. Excess Gibbs free energies and a-X relations for CO2-H2O fluids at 400°C and pressures to 400 MPa calculated from modified Redlich-Kwong and Lee-Kesler equations of state generally suggest significantly smaller positive deviations from ideality.